France and Geopolitics: A Complicated Story Threatened by EU and NATO Memberships - Гранпјерон, Матје (Napredak, 2025)
The author of this paper addresses French geopolitics, or today’s position of France in the context of its membership in the European Union and the NATO. The starting assumption is that the membership in these two organizations limits the French position and opportunities for reviving French geopolitics which formerly put forward national interests and the sovereignty of the state. Having in mind that the EU and the NATO are a threat to France’s true geopolitics, in the first part of the paper the author justifies his thesis, first in the context of France’s position in the EU and the NATO, and the in relation to the ideology of positivist liberal internationalism. In the second part, the author analyzes the introduction of geopolitics in the French educational system and recognizes advantages and disadvantages in the system itself. Finally, the author offers a solution to the foundation of the French geopolitical thought which should be based on glorious history and a patriotic elite.
Keywords: France; geopolitics; education; positivism; history; European Union; NATO